أسباب عزوف الطلاب عن الالتحاق بالمساق العلمي في التعليم الثانوي بمدينة الدويم ) من وجهة نظر المعلمين ) - د / محمد الأمين محمد يوسف كبر (White Nile Journal for Studies and Research, 2013)
All information coming from central or White Nile state ministry of education agree that the percentage of scientific students in secondary education is very low not more than 30%. This problem needs to be diagnosed so as to come to the the dealing with this problem reasons of this educational defect researcher used the descriptive approach and a questionnaire to collect the statistically data from secondary teachers in Eldueim town. SPSS program to have the results which the most researcher used ، activities students books the absence of labs :important of them are While the and educational and professional counseling to students teacher the availability of labs : most important recommendations are training and reopening of boarding houses in the country